ACCURACY INFLUENCE OF CHAIN GEARS ON THEIR WORKABILITY - Іващенко, Василь Трифонович; Витвицький, Василь Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We consider questions of influence accuracy of parts gear with the drive roller chains and accuracy of editing gears on their work ability. The parameters that determine the accuracy of the mounting of chain wheels! The estimation of the impact of stress concentration in the joints chain in his lifetime.